La composición del Ministerio Fiscal en España y en Francia: cuestiones de traducción y terminología - Delgado Pugés, Iván (Anales de Filología Francesa, 2010)
The translation of specialized texts demands translators to have a thematic knowledge related to many areas. In the case of the translation of legal texts, where the transmission of information is carried out between two different legal systems, a professional translator should possess special knowledge of the Law of both systems. This article aims to expose a brief summary of the figure of the French Ministère public and the Spanish Ministerio Fiscal, an organism that in both countries has as its mission that of promoting the operation of justice in the defence of the rule of law, of citizens’ rights and of the public interest as safeguarded by the law, as well as that of protecting the independence of the Courts and securing through them the satisfaction of social interest. To this end, in a first stage we will explain how this organism is articulated and organized in both systems, and in a second phase we will analyze if the existing differences may lead to translation or terminological problems that may hinder the translator’s work.